1990
DOI: 10.1177/0013916590225001
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Building in Wayfinding

Abstract: This article uses a limited example to demonstrate that studies of wayfinding and spatial learning can benefit from a more rigorous analytic description of building layout and exploration paths that exhibit their own pattern. In at least one case, search patterns are strongly shaped according to the degree of integration of each space and each choice node of the circulation system within the overall layout. Given this overriding trend, we formulate the idea of a search structure whereby the intelligible proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
221
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(237 citation statements)
references
References 12 publications
9
221
0
7
Order By: Relevance
“…That a configuration significantly affects movement at a microscopic level has also been discovered by researchers interested in space syntax (Hillier and Hanson, 1984). Peponis et al (1990) and, more recently, ul Haq (2001, make empirical studies of people movement in hospital environments. Peponis et al attempt a categorisation of a number of`rules' of navigation: (1) Avoid backtracking.…”
Section: Related Workmentioning
confidence: 73%
“…That a configuration significantly affects movement at a microscopic level has also been discovered by researchers interested in space syntax (Hillier and Hanson, 1984). Peponis et al (1990) and, more recently, ul Haq (2001, make empirical studies of people movement in hospital environments. Peponis et al attempt a categorisation of a number of`rules' of navigation: (1) Avoid backtracking.…”
Section: Related Workmentioning
confidence: 73%
“…Signage stimuli also facilitate navigation (Hölscher et al, 2006, O'Neill, 1991Passini, 1984;Peponis et al 1990;Titus & Everett, 1995;Weisman, 1981). Sorensen (2009) found that 80 percent of shoppers' in-store time is spent navigating and the remaining 20 percent is spent deciding which items to purchase; on this basis, it is likely that customers will be exposed to, and influenced by, signage material during both the navigation and decisionmaking stages of the in-store search process.…”
Section: Introductionmentioning
confidence: 99%
“…This has been found in homes [15] and in factories [26]. In terms of prediction, integration has been found to be predictive of aggregate movement, with integrated routes preferred to segregated routes during search tasks [27]. Some research has been done on space syntax measures as predictive of movement through virtual environments.…”
Section: The Axial Mapmentioning
confidence: 95%